2001
DOI: 10.1079/095442201108729240
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and bioefficacy of folate and folic acid in man

Abstract: Folic acid is important because supplementation around the time of conception has been proven to lower the risk of having offspring with a neural-tube defect. Furthermore, both dietary folate and folic acid decrease plasma total homocysteine concentrations. Elevated plasma homocysteine concentrations are considered to be an independent risk factor for cardiovascular disease. The aim of the present review is to give an overview of factors influencing bioavailability and bioefficacy (the proportion of ingested n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In the literature, there are more studies utilising folic acid compared to 5‐MTHF, likely because folic acid is more bioavailable than other forms of folate and stable which is beneficial for diet fortification. It is important to note that folic acid and other forms of folate such as 5‐MTHF act via distinct pathways of metabolism and that the mode of delivery and amount consumed can change the efficacy of both folic acid and folate . Indeed, in the present study, we show that only animals with LFA or high 5‐MTHF with SST diets demonstrated significantly reduced levels of plasma homocysteine levels compared to the folate deficient group.…”
Section: Discussionsupporting
confidence: 45%
“…In the literature, there are more studies utilising folic acid compared to 5‐MTHF, likely because folic acid is more bioavailable than other forms of folate and stable which is beneficial for diet fortification. It is important to note that folic acid and other forms of folate such as 5‐MTHF act via distinct pathways of metabolism and that the mode of delivery and amount consumed can change the efficacy of both folic acid and folate . Indeed, in the present study, we show that only animals with LFA or high 5‐MTHF with SST diets demonstrated significantly reduced levels of plasma homocysteine levels compared to the folate deficient group.…”
Section: Discussionsupporting
confidence: 45%
“…Several factors account for this, such as the fact that folate is ''trapped'' in the matrix of plant foods. 36 The absorption of dietary folate is estimated to be only about 50%, but this remains to be verified in well-designed experiments in humans.…”
Section: Folatementioning
confidence: 99%
“…Food products can be fortified to make up for the expected process loss, but the added active compounds may react with other food components, potentially reducing overall nutritional and organoleptic qualities (Salgueiro and others 2002; Xia and Xu 2005). The bioavailability of these active compounds can also be affected by their binding with the food matrix, the form of nutrient derivative available, and the gastrointestinal conditions that the compounds are subjected to (Ristow and others 1982; Hurrell 1997; Brouwer and others 2001; Basu and Donaldson 2003). To circumvent these problems, the fortified active compounds often need to be protected, using techniques such as spray‐drying microencapsulation, extrusion encapsulation, fluidized bed coating, coacervation, spray chilling, molecular inclusion using β‐cyclodextrin, protein precipitation, liposome entrapment and hydrogel entrapment (Gibbs and others 1999; Remondetto and others 2004; Yuliani and others 2004).…”
Section: Introductionmentioning
confidence: 99%